Znaczenie słowniczka tekstu aktu prawnego na przykładzie Kodeksu karnego skarbowego - Włodkowski, Olaf (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The aim of the article is to present the importance of the Glossary to the Polish Fiscal Penal Code Art. 53. The Author presents the important features of the Glossary, its meaning and specificity. The analysis leads the author to the conclusion that the editing of the glossary of the Article 53 of the Fiscal Penal Code has been influenced firstly by the relation between criminal fiscal law and fiscal law, and secondly by the autonomous character of the criminal fiscal law regulation in relation to general criminal law. In conclusion, the Author states that the Glossary to the Fiscal Penal Code plays an important role in the interpretation of criminal regulations of the special part of the Fiscal Penal Code. It is worth recognising that the legal regulation of the Glossary to the Fiscal Penal Code is a coherent, complete, orderly and necessary solution in criminal fiscal law.
Keywords: kodeks karny skarbowy; słowniczek wyrażeń kks